Efficient Multi-Stage Deployment of Ultra-Low Loss Fibers in Elastic Optical Networks - Li, Yongcheng; Chen, Wei; Bose, Sanjay Kumar; Shen, Gangxiang (Journal of lightwave technology, 2020)
Ultra-low loss (ULL) fibers allow high-quality signal transmission and are expected to become important candidates for new deployment of fiber links in an optical network. In our previous study, we investigated strategies for selecting network links to be deployed with ULL fibers in a single stage, subject to an annual operational budget. As a step further, this study considers such deployment in multiple stages, which corresponds to a scheduling problem of ULL fiber deployment. To this end, we cannot simply adopt a repetition of our previous single-stage deployment approach since it cannot tell which set of links are to be deployed with ULL fibers in each stage. Rather, we need to jointly consider the set and the order of links to be deployed in each stage so as to get a maximum overall gain in terms of time-weighted frequency slot (FS) usage. Also, the time taken for deploying each fiber link and the interval between neighboring deployment stages should be considered. To achieve a global optimization, we develop a mixed integer linear programming (MILP) model and look at three scheduling strategies which are physical length (PL), shortest route traversed (SRT), and maximum deployment gain (MDG) based strategies. We evaluate the performance of these strategies through simulations and find that the proposed MDG strategy performs best in terms of the total time-weighted FS usage. Results also show that there is an optimal number of deployment stages which provides maximum gain of spectrum usage while requiring few network re-optimizations.